Aloe vera and ofloxacin incorporated chitosan hydrogels show antibacterial activity, stimulate angiogenesis and accelerate wound healing in full thickness rat model. Issue 2 (2nd September 2022) - Khan, Ahmad; Andleeb, Anisa; Azam, Maryam; Tehseen, Saimoon; Mehmood, Azra; Yar, Muhammad
Abstract: Burns are potentially fatal and physically debilitating injuries, causing psychological and physical scars and result in chronic disabilities. A well vascularized wound bed is required to achieve complete and scar free wound closure. For many centuries, a variety of herbal plants have been used for wound healing, among these aloe vera (AV) has been found to be very effective in wound healing. Secondly, the main reason for delayed wound healing is bacterial infections. Ofloxacin (OX) has been reported as an active antibacterial drug for topical infections and it is effective against both positive and negative bacterial strains. In current research three different concentrations of OX (0.5, 2.5, and 5 mg) were loaded into chitosan (CS)/AV based hydrogels prepared by freeze gelation. The surface morphology of prepared CS/AV based OX loaded hydrogels were evaluated by scanning electron microscopy (SEM). In drug release analysis, 0.5 mg OX loaded hydrogel showed a sustained drug release behavior over 3 days period. An effective dose dependent antibacterial activity was exhibited by OX loaded hydrogels. Alamar Blue cells viability assay revealed that 0.5 mg OX hydrogel (CA 0.5 OX) showed comparatively better 3 T3 fibroblast cells proliferation as compared to CA 2.5 OX (2.5 mg OX) and CA 5 OX hydrogel (5 mg OX). Moreover, all OX loaded hydrogels showed good angiogenic activity in CAM bioassay while higher angiogenic potential was observed from CA 0.5 OX containing comparatively lower concentration of OX. These OX incorporated CS/AV based hydrogels are promising wound dressings for future clinical use. Abstract : Aloe vera and ofloxacin incorporated chitosan hydrogels and their biological evaluations.